2008
DOI: 10.1080/02841860802022976
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 as a tumor marker in breast cancer – An update

Abstract: Improvement of the management of breast cancer patients has high priority. In this regard, prognostic stratification needs to be improved in order to ensure proper medical treatment of all patients and furthermore predictors of response to chemotherapy are urgently needed. As new treatment opportunities emerge in the future this need will continue to grow. Thus, the search for molecular markers of prognosis and prediction is ongoing. Tissue Inhibitor of Metalloproteinases-1 (TIMP-1) has been suggested as a mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 48 publications
2
58
0
1
Order By: Relevance
“…TIMP1 inhibits apoptosis (28)(29)(30)(31) and protects human breast epithelial cells against both intrinsic and extrinsic apoptotic cell death via the focal adhesion kinase/phosphatidylinositol 3-kinase and MAPK signaling pathways, and thus may be oncogenic (32). Clinical studies using primary breast cancer cells revealed an association between high levels of TIMP1 mRNA or protein and a poor prognosis for patients with breast cancer (33)(34)(35). In addition, TIMP1 gene deficiency increased tumor cell sensitivity to chemotherapy-induced apoptosis (36).…”
Section: Discussionmentioning
confidence: 99%
“…TIMP1 inhibits apoptosis (28)(29)(30)(31) and protects human breast epithelial cells against both intrinsic and extrinsic apoptotic cell death via the focal adhesion kinase/phosphatidylinositol 3-kinase and MAPK signaling pathways, and thus may be oncogenic (32). Clinical studies using primary breast cancer cells revealed an association between high levels of TIMP1 mRNA or protein and a poor prognosis for patients with breast cancer (33)(34)(35). In addition, TIMP1 gene deficiency increased tumor cell sensitivity to chemotherapy-induced apoptosis (36).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to what the role of TIMP-1 in inhibiting the prometastatic factor MMP-9 might suggest, high TIMP-1 levels actually correlate with a worse prognosis and a faster progression of the disease. 47,48 This phenomenon seems to be related to the capability of TIMP-1 of promoting cell survival and proliferation of cancer cells, making it an appealing target for novel therapeutic strategies for the treatment of breast cancer, as well as fibrosis secondary to hypertension 49 or liver diseases. 50,51 Although several compounds are currently under investigation as TIMP-1 inhibitors, the potential side effects of such therapeutic approaches are still controversial and poorly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies revealed somewhat contradictory results, since both high and low levels of TIMP-1 in tumor tissue extracts were associated with a poor prognosis in breast carcinoma patients [18,19] . High preoperative serum levels of TIMP-1 were also a prognosticator of a poor outcome in breast carcinoma patients [20] , and a recent review suggested a predictive role of TIMP-1 in anticancer therapies according to preclinical data and preliminary clinical studies [21] .…”
Section: Introductionmentioning
confidence: 99%